Чужой ребенок: [роман] / Маша Трауб - Трауб Маша (Проза Маши Трауб, 2015)
Экземпляры: аб. ф.7 (20151009) / Инвентарный номер: 40903 / Цена: / Сис.шифр: 84(2=411.2)6 / Авт.знак: Т 65 / ГРНТИ: 17.82.31 / ББК: 84(2=411.2)6